Exploring Supervisors’ Attitudes of Working with Youth Engaged in an Inclusive Employment Training Program - Lindsay, Sally; Mcdougall, Carolyn; Sanford, Robyn (Développement Humain, Handicap et Changement Social / Human Development, Disability, and Social Change, 2012)
Background: Although employment is a right of citizenship, people with disabilities remain underrepresented in the workforce. Employment is especially important for people with disabilities because it can alleviate financial hardship, social isolation, improve confidence and quality of life. Most research exploring employers’ views of hiring employees with disabilities has focused on adults while little is known about employers’ experience of working with youth with disabilities. The purpose of this study was to explore supervisors’ views of working with an adolescent with disabilities as a part of an employment training program. Method: The sample was drawn from the supervisors of youth taking part in an employment training program, run through children’s rehabilitation hospital in a large urban centre. A descriptive questionnaire was sent to all supervisors who worked with a adolescent with disabilities as part of an employment training program. Thirty-six questionnaires were completed with a response rate of 92%. Results: Our findings show that most supervisors felt prepared when youth arrived and that supervising them did not take up much extra time. Some supervisors had a few initial concerns about workplace accommodations and workload but these were quickly resolved. Most supervisors who worked with youth with disabilities reported a positive experience and that having them in the workplace also had the added benefit of challenging some of their assumptions about people with disabilities. Conclusions: Our findings emphasize the importance of supervisors having an opportunity to work with a person with disabilities because it can help to break down negative attitudes and stereotypes.